Exoenzyme activity and possibility identification of Candida dubliniensis among Candida albicans species isolated from vaginal candidiasis. (September 2017) - Jafari, Maryam; Salari, Samira; Pakshir, Keyvan; Zomorodian, Kamiar
Abstract: Objectives: Vulvovaginal candidiasis (VVC) or vaginal candidiasis is a common fungal infection of the genitals causing inflammation, irritation, itching, and vaginal discharge. Common yeast infections are caused by the yeast species C. albicans. However, there are other species of Candida such as C. dubliniensis which are considered as the causative agents of this infection. Hydrolytic enzymes such as proteinase and coagulase are known as virulence factors. The aim of this study was the molecular confirmation and differentiation of C. dubliniensis among C. albicans strains isolated from women with vulvovaginal candidiasis by PCR-Restriction Fragment Length Polymorphism (PCR-RFLP) and the evaluation of proteinase and coagulase activities. Methods: A total of 100 C. albicans strains isolated from women with vulvovaginal candidiasis referred to Shiraz medical clinics were enrolled in the study. All the isolates were primarily identified by conventional methods. PCR-RFLP method was used for the confirmation and identification of C. albicans and C. dubliniensis . Moreover, in vitro proteinase and coagulase activities of these isolates were evaluated using bovine serum albumin media and classical rabbit plasma tube test. Results: As a result, PCR-RFLP identified 100% of the isolates as C. albicans, and no C. dubliniensis could be identified in this study. 84% of the isolates showed proteinase activity, whereas coagulase activity was only detected in 5% of the isolates. Conclusions: This study reveals that C. dubliniensis plays no role in vaginal candidiasis in Iranian patients. Proteinase production could be an essential virulence factor in C . albicans pathogenicity, but coagulase activity has less potential in this matter. Highlights: C. dubliniensis was not identified among C. albicans isolates obtained from patients with vulvovaginal candidiasis. PCR-RFLP method with Msp I and Bln I enzymes is a rapid and reliable method for distinguish between C. albicans and C. dubleniensis. Proteinase production was an essential virulence factor in C.albicans species but, coagulase activity has less potential in this matter.